ANALYSIS OF PRE-PROSPEROUS HOUSEHOLD CONSUMPTION DIVERSITY IN LAMPUNG PROVINCE (SUSENAS DATA ANALYSIS, 2019) - Nugrahanti, Desmarita; Sayekti, Wuryaningsih Dwi; Lestari, Dyah Aring Hepiana (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2024)
Food security has clear goals and impacts on efforts to improve nutrition and improve community welfare.  To achieve this, diversification of food consumption plays an important role. Diversification of food consumption has a role in efforts to improve nutrition and to obtain quality human beings and reduce dependence on certain commodities. However, consumption pattern is different to each household depending on its income levels. The majority of household welfare levels in Lampung Province are categorized as pre-prosperous households. The economic situation (income) of pre-prosperous households can affect the food choice. If the food choice is inappropriate, the fulfillment of nutritional quality is not optimal and can affect the quality of human resources. As a result, research on this topic was critical, particularly in lower middle-class households especially pre-prosperous households. The goal of this study was to examine the amount of consumption diversification and its determinants among the pre-prosperous households. Secondary data from the 2019 SUSENAS raw data were used in this investigation. This survey included 2,792 households as samples. The Berry Index was employed to quantify the diversity of food consumption, and binary logistic regression analysis was performed to study its determinants. The amount of food consumption diversity among pre-prosperous households in Lampung Province was moderate. The Berry Index had an average value of 0.827. Household income, education of the head of the household, education of the mother, gender of the head of the household, and type of region all had a positive effect on household food consumption diversity, whereas the number of household members had a negative effect.  Based on these results, comprehensive policies are needed with clear targets and programs that contribute to increasing employment opportunities and income so that family consumption is more diverse and of high quality.  In addition, it is also necessary to increase the contribution of education both through formal and non-formal education, and promotion in the implementation of counseling or socialization on diversification of food consumption.